Upaya Meningkatakan Kompetensi Profesional Guru Bahasa Indonesia dalam Menerapkan Model Problem-Based Learning SMP Negeri 1 Sitellu Tali Urang Julu T.A. 2022/2023 - Adong Gifta Ginting (Fakultas Keguruan Ilmu Pendidikan Universitas HKBP Nommensen, 2023)
This research aims to improve the professional competence of Indonesian language subject teachers at SMP Negeri 1 Sitellu Tali Urang Julu in implementing the Problem-Based Learning Model with Supervision. The research was carried out in two cycles, each cycle consisting of four stages, namely: planning, implementation, observation and reflection. From data analysis it was found that there was an increase in teacher activity and competence in implementing the PBL model from cycle I to cycle II. Achievement of performance indicators can be found in action II. In the initial condition, from 54.00 with poor score criteria it increased to 66.00 with sufficient score criteria and 76.00 with good score criteria, in the learning implementation aspect the average score was 55.21 with poor score criteria increased to 65.43 with sufficient score criteria and 75.43 with good score criteria in the second cycle, in the aspect of learning outcomes assessment from an average of 53.58 with poor score criteria to 65.42 with sufficient score criteria and 77.42 with good score criteria as well as classroom management aspect of 54, sufficient and 75.83 with good score criteria. Thus, it can be assumed that Model 83 with the score criteria is less than 66.83 with the score criteria. Academic supervision development by the principal can increase the competence of Indonesian Language teachers at SMP Negeri 1 Sitellu Tali Urang Julu,